INSIGHTS ON THE INFLUENCE OF PHYLOGENETIC ON THE RELATIVE GROWTH USING Atherinella brasiliensis AS A TOOL - Renato Luiz BOT NETO; Barbara Maichak de CARVALHO; Roberto SCHWARZ JÚNIOR; Henry Louis SPACH (Boletim do Instituto de Pesca)
The length–weight relationships (LWR) are important tools for ichthyology, they are useful to demonstrate the environmental influence on growth. In this study we estimate the LWR of the Atherinella brasiliensis in the shallow areas of the São Francisco river estuary and compare the growth of this specie in different environments of the Brazilian coast. Specimens of Brazilian silverside (A. brasiliensis, n = 3483), between 2.1 and 13.6 cm in length, were caught in the shallow areas of the São Francisco River estuary between May 2017 and April 2018. The length-weight ratio of the species was represented by the equation y=0.0047x3.0913. Frequency distribution indicates that the species is present in the shallow areas of the São Francisco River estuary in all its ontogenetic stages and apparently reproduces throughout the year with constant input of recruits into the population. Von Bertalanffy’s growth model and longevity were adjusted to reach asymptotic length (L∞) of 14.7 cm, growth coefficient (K) of 0.91 year-1 and longevity (A95) of 3.25 years. The analysis of variance revealed differences for the maximum total length. However, the differences found between the present study and data available in the literature appear to be caused by environmental and methodological differences.